Schizophrenia Etiological Factors and Their Correlation with the Imbalance of the Immune System: An Update: Schizophrenia and the Imbalance of the Immune System: Schizophrenia and the Imbalance of the Immune System - Lotfi, Noushin; Rezaei, Nahid; Rastgoo, Elham; Khodadoustan Shahraki, Babak; Zahedi, Ghazaleh; Jafarinia, Morteza (Galen Medical Journal, 2023)
Schizophrenia (SZ) is a severe psychiatric disorder associated with a dysregulation of the immune system. Immune-related genes and environmental factors including stress, food, infections, and microbiota, alter the immune system’s homeostasis and play a role in SZ pathogenesis. The most distinctive feature in the pathophysiology of the disease is a shift in the T helper 1(Th1)/Th2 balance toward Th2 dominance in the immune system. Also, microglial and Th17 cell activation cause inﬂammatory responses in the central nervous system (CNS). Antibodies play a role in the pathophysiology of SZ and give more evidence of a link between humoral immune reactivity and the disease. Accordingly, an imbalance in cytokine activities and neuroinflammation has been considered the main contributor to the pathogenesis of the SZ. Overall, the deregulation of the immune system caused by genetic, environmental, and neurochemical effects may all play a role in the etiology of SZ. This review summarized the etiological factors for SZ and discussed the role of immune responses and their interaction with genetic and environmental factors in SZ pathogenesis.